EMPOWERING STUDENTS ACCESS CENTER (SAC) IN SUPPORTING ENGLISH LEARNING - Nor, Hidayah; Sari, Afifah Linda (Jurnal As-Salam, 2023)
This study focuses on conducting a need analysis to explore the role and effectiveness of the Student Access Center (SAC) in supporting English Education Department students’ learning endeavors. The SAC is a place and an essential resource hub catering to students’ academic, personal, and professional needs. The data was collected using a survey design from a questionnaire given to 51 English Education Department students at UIN Antasari Banjarmasin. The questionnaire included five Likert-scale-based choices regarding the student’s learning needs about the role of SAC. The investigation delves into various aspects, including the collection of books provided by the SAC, its accessibility, and the extent to which it addresses students’ needs both inside and outside the classrooms. The study examines students’ perceptions of the SAC’s facilities in enhancing their learning, the circulation service, and the function of SAC. Findings from this study contribute to a comprehensive understanding of the SAC’s significance in supporting English Education Department students. Ultimately, this research aims to foster a conducive learning environment that maximizes students’ academic achievements and success.